Relevance of the Analysis of the Financial Statements for Business Decision-Making - Sandra Natalia Gallego Gomez; Orlando Carmelo Castellanos Polo (MultiTech Publisher, 2023)
The importance of the analysis of financial statements for business decision making will be determined, taking into account the financial indicators, to demonstrate which are the methodologies used to perform a financial analysis, in order to provide capabilities of opportunities that allow growth in the current situation due to the pandemic caused by the Covid-19